Fluid catalytic cracking - Ihediwa, Chinasaekpere (Kansas State University, 2021)
Catalytic cracking is a process in which hot, powdered catalyst is intimately mixed with a hot petroleum-derived feedstock, then transported through a turbulent reaction zone with a reactant residence time of 1-5 seconds. It has enabled refineries to produce a tremendous amount of high-octane number gasoline from high-boiling stocks using catalysts. It progresses through a carbocation to produce active species on acidic catalytic sites. This process involves acidic catalysts like zeolite in the breaking up of long carbon chains of n-alkanes into shorter chains alkanes like iso-alkanes, cycloalkanes, and aromatics. Other products like Liquefied Petroleum Gas (LNG), cycle oils, and olefin-rich light hydrocarbons (C3, C4) are also produced. The olefin-rich light hydrocarbons are used as petrochemical feedstock, and as reactants in alkylation and polymerization reactions. Refining shale crude oil presents a very difficult challenge because of its very low hydrogen to carbon ratios. The production of good quality gasoline, kerosene, and diesel are very poor due to high levels of heavier components such as asphaltene and Sulphur-containing species. Many petroleum refineries combine two methods in order to convert and refine this heavy crude oil: conventional fluidized catalytic cracking followed by residue fluidized catalytic cracking, allowing heavy oils with high viscosity to be process and refined.
Keywords: Fluid Catalytic Cracking (FCC)